Hsa_circ_0002348 regulates trophoblast proliferation and apoptosis through miR-126-3p/BAK1 axis in preeclampsia - Jizi Zhou; Ying Zhao; Ping An; Huanqiang Zhao; Xiaotian Li; Yu Xiong (Journal of Translational Medicine, 2023)
Abstract Background Preeclampsia is a common pregnancy complication characterized by high blood pressure and damage to organs. Abnormal placenta and vascular function can lead to preeclampsia. Accumulating evidence has suggested a potential link between circular RNAs (circRNAs) and preeclampsia. As a placenta and endothelial-expressed circRNA, hsa_circ_0002348, may be promising to be the novel molecular target for preeclampsia. However, the function and mechanism of hsa_circ_0002348 in preeclampsia has not been elucidated. Materials and methods An overlap analysis of two circRNA profiles from placenta and endothelial cells was used to identify a functionally unknown circRNA, hsa_circ_0002348. Quantitative real-time PCR (qRT-PCR) and in situ hybridization (ISH) were used to detect its expression in the trophoblast cells and placental tissues. The mouse model of lipopolysaccharide (LPS)-induced preeclampsia was established to determine the in vivo role of hsa_circ_0002348. RNA immunoprecipitation (RIP), Luciferase reporter assay, qRT-PCR, western blot, gain- and loss-of-function and rescue experiments were conducted to uncover the role of hsa_circ_0002348 and its interaction with miR-126-3p and BAK1 in regulating trophoblast proliferation and apoptosis. Fluorescence in situ hybridization (FISH) and Immunohistochemistry (IHC) were performed to examine the expression of miR-126-3p and BAK1 in mice and human placentas, respectively. Results Hsa_circ_0002348 was significantly increased in the preeclampsia placentas, and positively correlated with the severity of preeclampsia patients’ clinical manifestations. Its overexpression exacerbated preeclampsia-like features in the mouse model of LPS-induced preeclampsia. Functionally, hsa_circ_0002348 was found to inhibit trophoblast proliferation and promote trophoblast apoptosis. Mechanistically, hsa_circ_0002348, as an endogenous miR-126-3p sponge, upregulated the expression of BAK1. Additionally, both hsa_circ_0002348 knockdown and miR-126-3p overexpression enhanced the mammalian target of rapamycin (mTOR) and ERK1/2 signaling pathway. Conclusions Hsa_circ_0002348 might be a novel regulator of trophoblast proliferation and apoptosis through miR-126-3p/BAK1 axis in preeclampsia, which may serve as a potential target for detecting and treating preeclampsia.